The common market, the internal market and the single market, what's in a market? - Mortelmans, Kamiel (1998)
Describes the realization of the Internal Market from 1957 to 1997. Discusses the Action Plan of the Commission and the results of the European Council and the Intergovernmental Conference of Amsterdam. Assesses the renewed commitment to the single market.